Further studies on the physiology of Azotobacter paspali and its dependence on the plant (Paspalum notatum) - Machado, Walter Coutinho; Döbereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
A number of experiments were carried out to explain the specific stimulating effect of Paspalum notatum on Azotobacter paspali growth. Natural occurrence of A. paspali was studied in the rhizosphere of Cynodon dactylon and Hyparrhenia rufa growing in consorciation with Paspalum notatum. A decrease of these bacteria was observed in the rootsurface soil of those grasses when compared with rhizosphere soil, confirming the specific effect on these bacteria of P. notatum. In a greenhouse experiment, survival of A. paspali was studied in pots with soil collected under Paspalum swards with and without liming and in pots with sand. Soil collected under Paspalum was less injurious than sand although the pH of the soil was lower. Liming the soil still improved conditions for A. paspali growth. When Paspalum notatum was planted in the pots, bacteria survival was satisfactory, sterilized plants poorer than natural ones and inoculated seedlings better than uninoculated ones. Rhizoplan samples contained higher numbers of the organisms than rhizosphere soil. All these differences became more pronounced in sand. In laboratory experiments the effect of root exudate of P. notatum and pH levels were studied in liquid culture medium. Good growth of. A. paspali was observed to be dependent on maintaining a quite narrow pH range (6.7 to 7.0). Increasing amounts of root exudate stimulated growth of this organism up to 200% of the original solution. The active substances were resistant to autoclaving at 120°C for 30 minutes thereby excluding the possibility that they are natural enzymes. Production of a yellow pigment was reduced by the root exudate.